Cerebral Iron Accumulation Is Not a Major Feature of FA2H/SPG35. Issue 1 (18th February 2015) - Marelli, Cecilia; Salih, Mustafa A.; Nguyen, Karine; Mallaret, Martial; Leboucq, Nicolas; Hassan, Hamdy H.; Drouot, Nathalie; Labauge, Pierre; Koenig, Michel
Abstract: Mutations in the fatty‐acid 2‐hydroxylase ( FA2H ) gene cause an autosomal recessive spastic paraplegia (SPG35), often associating with cerebellar ataxia; cerebral MRI may show iron accumulation in the basal ganglia, leading to the inclusion of SPG35 among the causes of neurodegeneration with brain iron accumulation. This finding was initially considered strongly relevant for diagnosis, although its frequency is not yet established. We found 5 novel patients (from two families) with mutations in the FA2H gene: none of them showed cerebral iron accumulation (T2‐weighted images performed in all; T2 gradient‐echo in 2); notably, in 1 case, iron accumulation was absent even after 18 years from disease onset on both T2 gradient‐echo and susceptibility‐weight MRI sequences. Cerebral iron accumulation is not a prominent feature in SPG35 and is not always dependent on disease duration; its absence should not discourage from evoking this diagnosis.